1997
DOI: 10.1080/096132197370345
|View full text |Cite
|
Sign up to set email alerts
|

Window and roof configurations for comfort ventilation

Abstract: This paper assesses the applicability of some architectural design elements to provide comfort ventilation in humid tropical regions: size and location of windows, building eaves and roof shapes for a single unit house. Most window and roof con gurations are suf cent to produce only a slightly more comfortable level although they can certainly increase the indoor air velocity. The improvement of indoor air velocity can minimize the physiological effect of the high humidity. Among the tested models, the room wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…Less studies focused on buildings with a flat roof and with asymmetric opening positions located in the facade (group 2); some examples are [23,[25][26][27]. Several studies analyzed the influence of the roof shape but with symmetric opening positions (in terms of height in the facade; group 3) [31][32][33][34][35][36]. Finally, quite some studies focused on buildings with a pitched roof and asymmetric opening positions (group 4) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Less studies focused on buildings with a flat roof and with asymmetric opening positions located in the facade (group 2); some examples are [23,[25][26][27]. Several studies analyzed the influence of the roof shape but with symmetric opening positions (in terms of height in the facade; group 3) [31][32][33][34][35][36]. Finally, quite some studies focused on buildings with a pitched roof and asymmetric opening positions (group 4) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [14,15]). Kindangen [14,15] performed Computational Fluid Dynamics (CFD) simulations and observed that in buildings with symmetric opening locations (inlet and outlet openings located at the same height) the use of eaves can increase the cross-ventilation flow rate.…”
Section: Introductionmentioning
confidence: 96%
“…Typical building façades include a venturi-shaped roof [13], wind catchers [9,[14][15][16], a ventilation shaft [17], wing walls [8], a balcony [7,10,11,18], and eaves [5,6,21]. Prajosan and Sharples [17] proposed a ventilation shaft system to increase the indoor air velocity and thermal comfort in a single-sided residential unit.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have utilized the aerodynamic potential of building façades to investigate their enhancement effect on indoor and outdoor airflow exchanges for both cross and single-sided ventilation buildings [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Typical building façades include a venturi-shaped roof [13], wind catchers [9,[14][15][16], a ventilation shaft [17], wing walls [8], a balcony [7,10,11,18], and eaves [5,6,21].…”
Section: Introductionmentioning
confidence: 99%